1902
DOI: 10.1002/aja.1000020107
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac glands of mammals

Abstract: When we consider the immense amount of energy that has been expended on the investigation of the gastric glands since the discovery of the chief cells by Heidenhain and Rollet in 1810, it is a matter for some surprise that so little interest should have been aroused in the small zone of glands surrounding the cardiac orifice of the stomach, now generally known as the cardiac glands. This fact is all the more surprising when we remember that, in some mammals, these glands are by no means restricted to the narro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

1906
1906
1987
1987

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…In the esophagus, the presence of mucous glands was reported in the early period of this century with considerable species variations [7], In man, the glands are detected early in the embryo [9]: their distribution in esophageal glands proper and in esophageal cardiac glands is well established [1,3,7,16], as well as the large individual variations of their number [1]. The study of mucosubstances in these cells was limited as for now to very short re ports: positivity of the mucicarmine reaction [1], and presence of sulfate esters [5], This work illustrates the presence of sialo-and sulfomucins in the esophageal glands proper and at the esophagogastric junction in the eso phageal cardiac glands.…”
Section: Discussionmentioning
confidence: 99%
“…In the esophagus, the presence of mucous glands was reported in the early period of this century with considerable species variations [7], In man, the glands are detected early in the embryo [9]: their distribution in esophageal glands proper and in esophageal cardiac glands is well established [1,3,7,16], as well as the large individual variations of their number [1]. The study of mucosubstances in these cells was limited as for now to very short re ports: positivity of the mucicarmine reaction [1], and presence of sulfate esters [5], This work illustrates the presence of sialo-and sulfomucins in the esophageal glands proper and at the esophagogastric junction in the eso phageal cardiac glands.…”
Section: Discussionmentioning
confidence: 99%
“…1983: Clerc andMei, 1983] and pathology [Bishop el al.. 1979]. Bensley [1902] concluded that the width of the cardiac gland region depends upon the species of animal. He also staled that typical cardiac glands con tain only mucous cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cardiac glands of the human stomach are branched tubular glands w'hich are organized into lobule like complexes by the connective tissue of the lamina pro pria [Miyagawa. 1920: Krause etal.. 1978, Since Bensley's [1902] description of the cardiac glands of mammals, no one has studied these glands in detail. This is especially true in the cat, even though it has been used recently as an experimental animal [Biancani et al.…”
Section: Introductionmentioning
confidence: 99%
“…These studies encompassed several species including man [Oppel, 1896: Bensley, 1902: Miyagawa, 1921: Plenk. 1933Babkin, 1950;Bargmann, 1956;Grossman, 1958;I960], The gastric pits (foveolae) of the pyloric gland area are of greater depth than other regions of the stomach.…”
Section: Introductionmentioning
confidence: 99%